Faktor-Faktor Yang Mempengaruhi Perilaku Ramah Lingkungan Siswa di Madrasah Aliyah Negeri 3 Kota Padang - Antikka Yusadi; Nefilinda; Trina Febriani (Jurnal Masyarakat Maritim, 2023)
This research is based on students' environmentally friendly behavior which needs to be re-directed on the importance of environmental knowledge, attitudes and awareness, especially in the madrasah environment which is a space for students to increase their insight and knowledge. This research aims to analyze and describe the influence of environmental knowledge, environmental care attitudes and environmental awareness on students' environmentally friendly behavior. The research method used was descriptive. The research used a population of 112 students and to determine the sample size, it was determined using Slovin's theory, so there were 88 student samples. From the research results, the following conclusions can be drawn: 1. There is a significant influence of the value of tcount > ttable (5.239 > 1.986) and the significance is 0.000 < 0.05 so it can be concluded that H0 is rejected and H1 is accepted. 2. There is a significant influence of the environmental care attitude variable on environmentally friendly behavior with the value showing tcount > ttable (2.417 > 1.986) and seen from the significance level of 0.000 < 0.05 so it can be concluded that H0 is rejected and H1 is accepted. 3. There is no significant influence of the environmental awareness variable on environmentally friendly behavior with a value of tcount < ttable (0.013<1.986) and a significance level of 0.018 <0.05 so it can be concluded that H0 is accepted and H1 is rejected. 4. There is an influence of environmental knowledge (X1), environmentally caring attitude (X2) and environmental awareness (X3) simultaneously have a significant effect on Environmentally Friendly Behavior (Y) with a calculated F value of 25.394 with a significance level of 0.000. Because Fcount is greater than Ftable (25.394 > 2.319), then Ho is accepted..